Urinary Intestinal Fatty Acid-Binding Protein Can Distinguish Necrotizing Enterocolitis from Sepsis in Early Stage of the Disease - Stepan Coufal; Alena Kokesova; Helena Tlaskalova-Hogenova; Jiri Snajdauf; Michal Rygl; Miloslav Kverka (Journal of Immunology Research)
Necrotizing enterocolitis (NEC) is severe disease of gastrointestinal tract, yet its early symptoms are nonspecific, easily interchangeable with sepsis. Therefore, reliable biomarkers for early diagnostics are needed in clinical practice. Here, we analyzed if markers of gut mucosa damage, caspase cleaved cytokeratin 18 (ccCK18) and intestinal fatty acid-binding protein (I-FABP), could be used for differential diagnostics of NEC at early stage of disease. We collected paired serum (at enrollment and week later) and urine (collected for two days in 6 h intervals) samples from 42 patients with suspected NEC. These patients were later divided into NEC (n=24), including 13 after gastrointestinal surgery, and sepsis (n=18) groups using standard criteria. Healthy infants (n=12), without any previous gut surgery, served as controls. Both biomarkers were measured by a commercial ELISA assay. There were no statistically significant differences in serum ccCK18 between NEC and sepsis but NEC patients had significantly higher levels of serum and urinary I-FABP than either sepsis patients or healthy infants. Urinary I-FABP has high sensitivity (81%) and specificity (100%) and can even distinguish NEC from sepsis in patients after surgery. Urinary I-FABP can be used to distinguish NEC from neonatal sepsis, including postoperative one, better than abdominal X-ray.